Modeling motherhood in Weimar Germany : political and psychological discourses in women's writing - Calvert, Katherine E. (Rochester, New York : Camden House, 2023)
"Reveals how socialist discourses and psychoanalytic ideas shaped the modern models of motherhood envisioned by left-wing and socially critical women writers working in the Weimar press and literary spheres. Women's experiences and opportunities in the Weimar Republic (1919-1933) were shaped by tensions between advances in women's rights and widespread adherence to conservative notions of gender roles and women's maternal duty. This book explores these tensions, which were particularly pronounced on the political left, by analyzing socialist and socially critical women writers' interventions in contemporary debates on gender and women's role in society. For women in Weimar Germany, writing represented a subversive medium through which they could individualize reproductive politics and imagine modern models of mothering. Relatable and aspirational mothering practices and mother figures feature in the literary and journalistic texts examined in this book. Theoretical and instructional works (by Alice Rühle-Gerstel and Henny Schumacher) and examples from the Social Democratic women's magazine Frauenwelt demonstrate how women writers adopted and adapted emerging psychological ideas to position their texts as modern and authoritative. A close analysis of critically neglected didactic texts (by Hermynia Zur Mühlen, Maria Leitner, Elfriede Brüning, and Else Kienle) and socially critical popular fiction (by Irmgard Keun, Vicki Baum, and Gabriele Tergit) exposes how women writers envisaged models of motherhood and family that were compatible with their political beliefs and modern lifestyles. This book reveals a pragmatic discourse that advocated progressive policies regarding reproductive choice and the rights of single mothers while leaving notions of women's maternal nature and duty largely unchallenged"--
The Psychology and Politics of Mothering: Alice Rühle-Gerstel's Das Frauenproblem der Gegenwart -- Women's Rights and Responsibilities as Mothers: Perspectives from the Left-Wing Women's Press and Non-Fiction Writing -- Women's Literary Interventions in Abortion Debates -- Family and Politics in Communist Didactic Fiction -- Intergenerational Tensions and New Women as Mothers in Popular Fiction.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 18, 2023).
JSTOR
Keywords: Motherhood -- Social aspects -- Germany -- History -- 20th century; Women -- Germany -- Social conditions -- 20th century; Women -- Political activity -- Germany -- History -- 20th century; Sex role -- Germany -- History -- 20th century; German literature -- Women authors -- History and criticism; Germany -- History -- 1918-1933.; Maternité -- Aspect social -- Allemagne -- Histoire -- 20e siècle.; Femmes -- Allemagne -- Conditions sociales -- 20e siècle.; Femmes -- Activité politique -- Allemagne -- Histoire -- 20e siècle.; Rôle selon le sexe -- Allemagne -- Histoire -- 20e siècle.; Allemagne -- Histoire -- 1918-1933.; German literature -- Women authors; Motherhood -- Social aspects; Sex role; Women -- Political activity; Women -- Social conditions; Germany; 1900-1999; Criticism, interpretation, etc; History